Reading Interests of High School Students during the Pandemic Covid-19 - Aveny Septi Astriani; Agi Ahmad Ginanjar; Muhsiyana Nurul Aisyiyah (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
Reading interest is different from reading habits and reading culture. Reading interest will turn into a reading habit if appropriate reading materials and sufficient time to read are available. This study aims to describe the reading interest of senior high school students during the pandemic Covid-19 based on emotional factor, self-motivation factor, and social factor using qualitative descriptive research. The technique used was a survey technique by distributing questionnaires. The sample consisted of 700 high school students selected randomly. The sample was distributed into several areas representing all districts, cities, and high school type such as senior high school, vocational high school, and Madrasah Aliyah (Islamic-based senior high school) by using the area cluster sampling technique. The data were presented using tables and sentence descriptions. The results of this study show that the reading interest of senior high school students during the pandemic was considered good from motivational factor, emotional factor, social factor, and the three factors simultaneously with the average score respectively being 3.47; 3.70; 3,40 and 3.53. The students' reading interest is influenced trainings aimed at increasing students' reading interest during the pandemic, technology, pandemic situation, and cognitive development for high school students which were classified as better than that of middle and elementary school students.